A história da matemática como ferramenta no processo de ensino-aprendizagem da matemática - Santos, Claudimar Abadio dos (2007)
The objective of this assignment is to display the possibilities to use the Mathematics History in classrooms, as a tool to motivate and support the process of teaching-learning this subject. In a order to this, some researches have been performed in books, thesis, dissertations and articles over this subject, and also an investigation on how professors deal with the possibility to use the Mathematics History in grades and courses that they work with. Some concepts will be analyzed in order to prove the importance of Mathematics contextualization aiming towards an efficient and significant teaching for the scholar. We will also express specifically the use of the Mathematics History as a factor of motivation an contextualization in the Math study, as well as some correct or incorrect ways to apply this History. Positive an negative aspects of the use of Mathematics History will be observed, under different angles, in order to measure the pertinence or disuse of the Mathematics History in classes